The distribution of village names based on pre-Christian Finnic personal names in the northern Baltic Sea area - Raunamaa, Jaakko (Finnisch-Ugrische Forschungen, 2020)
The article studies pre-Christian Finnic anthroponyms and their spread in the northern Baltic Sea area at the end of Middle Ages (c. AD 1520). This is done by analysing village names based on pre-Christian Finnic personal name elements. The primary research material consists of various editions of documents from the 15th and 16th centuries. The analysis demonstrates that village names based on pre-Christian Finnic anthroponyms are most densely located in Varsinais-Suomi, Häme, Northern and Eastern Estonia, Southern Karelia, the Karelian Isthmus and Eastern Ingria. The first four areas are home to significant Iron Age settlements. It seems that the use of the pre-Christian Finnic name elements under investigation originally started in these areas and spread eastwards.